Understanding features and benefits: An analysis of ideational meaning in youtube video advertisements - Alma Luthfiyyah Kiswanto; Riesky Riesky; Ernie D. A. Imperiani (Universitas Pendidikan Indonesia (UPI), 2020)
Features and Benefits are the two important elements in advertising that marketers usually use to get the audiences’ attention about products or services that they try to offer. By employing a features and benefits theory by Bly (2005) along with transitivity theory by Halliday Matthiessen (2004), this study focused on the way features and benefits are distributed and represented in smartphones, e-commerce, and makeup YouTube video advertisements. This study used a descriptive qualitative method to explain or interpret the data. This study discovered that features occur more dominantly with 63.27% in smartphones, 51.11% in e-commerce and 54.84% in makeup YouTube video advertisements. Meanwhile benefits are only used 36.73% in smartphones, 48.89% in e-commerce and 45.16% in make up YouTube video advertisements. In other words, all of these three categories used more features than benefits in advertising their products and services. These findings indicate that features meet the potential buyers’ needs and solve their problems as features describe the important aspects that potential buyers are looking for. As for the transitivity process, these three categories of YouTube video advertisements frequently use both relational process and material process. The relational process expresses the product features and attributes, while the material process suggest that these advertisements are typically concerned with actions and events. This is in line with the advertising copywriter’s strategic goal which generally aims to persuade potential buyers and arouse their interest in the products and services being advertised.Keywords: Benefits, copywriting, features, transitivity, YouTube video advertisements